A two-layer network model of the evolution of public risk perception of emerging technologies - Xiaqun Liu; Xiaoyue Qiu; Yaming Zhuang (Heliyon)
To fully comprehend public understanding of emerging technologies and their risks, from the stakeholder perspective, this study categorizes the public into primary and secondary stakeholders. Considering the impact of the spread of risk events on public risk perception of emerging technologies, this study adopts complex network theory to construct a two-layer network model consisting of “the spread of risk events–the evolution of public risk perception” of emerging technologies. The evolutionary threshold of public risk perception is analysed using the microscopic Markov chain approach. The influence of public composition and the spread of risk events on the evolution of risk perception is further verified through a simulation. The results of the study are as follows: First, public risk perception of emerging technologies tends to stabilise quickly. Second, the threshold and steady state of the evolution of public risk perception are influenced by the spread of risk events. Third, as the proportion of primary stakeholders or risk perception gap between primary and secondary stakeholders increases, the threshold for the evolution of public risk perception of emerging technologies increases, and the proportion of the public who think that emerging technologies are risky gradually decreases.